1994
DOI: 10.1007/bf01700277
|View full text |Cite
|
Sign up to set email alerts
|

Interventional antimicrobial therapy in febrile neutropenic patients

Abstract: In this prospective multicenter trial, treatment strategies for 1573 patients with neutropenia < 1000/microliters and fever > or = 38.5 degrees C after cytotoxic chemotherapy were compared. Patients with unexplained fever were randomized to a three-phase sequential study for different established drug regimens. If an infection could be defined microbiologically or clinically, treatment modifications were determined. In phase I, treatment for all patients consisted of acylaminopenicillin (PEN) plus aminoglycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 61 publications
3
51
1
6
Order By: Relevance
“…Published rates of BSIs in patients undergoing HSCT are reported to be higher than rates from studies including patients receiving induction/consolidation chemotherapies (29-39% versus 10-30%, respectively). 10,13,[25][26][27] In our analysis, there was a trend toward more BSIs in the allogeneic HSCTs, without a statistically significant difference in the McNemar model, which may be explained by the small number of patients available for this analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…Published rates of BSIs in patients undergoing HSCT are reported to be higher than rates from studies including patients receiving induction/consolidation chemotherapies (29-39% versus 10-30%, respectively). 10,13,[25][26][27] In our analysis, there was a trend toward more BSIs in the allogeneic HSCTs, without a statistically significant difference in the McNemar model, which may be explained by the small number of patients available for this analysis.…”
Section: Discussioncontrasting
confidence: 54%
“…58 A later report maintained the empirical therapy for at least two afebrile days in patients with increasing neutrophil count or seven days in patients with persistent neutropenia. 59 Two more recent prospective studies in children found that discontinuation of antibiotics before marrow recovery did not increase fatality due to bacterial infections. In the first study, children considered to be at low risk for bacterial infections (no identifiable focus, hemodynamic stability, negative admission cultures, and serum C-reactive protein (CRP) < 40 mg/L on Days 1 and 2; normal <10) were randomized on Day 3 of empirical antibiotic therapy to stop antibiotic therapy (n=36) or to continue (n=39) until the resolution of fever and neutropenia.…”
Section: Duration Of Antibiotic Therapy In Febrile Neutropeniamentioning
confidence: 99%
“…8 The success of antibiotic treatment in leukopenic patients depends on the leukocyte recovery. 9 The transplantation of autologous hematopoietic stem cells can rescue the host hematopoietic functions after high-dose chemotherapy. High-dose chemotherapy showed favorable disease control and survival in patients with multiple myeloma or lymphoma.…”
Section: Introductionmentioning
confidence: 99%